2016
DOI: 10.3400/avd.oa.16-00040
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Improvement in Patients Undergoing Carotid Endarterectomy for Atherosclerotic Occlusive Carotid Artery Disease

Abstract: Objectives:To assess the improvement in neurocognitive functions after carotid endarterectomy (CEA) under local anesthesia (LA) in patients with carotid bifurcation occlusive disease. Place and duration of study: Department of Vascular Surgery, Combined Military Hospital Lahore from January 2013 to January 2015. Patients and Methods: A total of 79 patients with carotid artery occlusive disease, having no history of major stroke, depression, or dementia underwent CEA under LA. Cognitive functions were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…The rate of carotid shunt placements was comparable between the intervention and control groups (7/30 (23.3%) vs. 4/30 (13.3%), respectively; p = 0.51). Although the duration of carotid cross-clamping did not differ between the intervention and control groups (37 (32-44) vs. 37 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) min, p = 0.98), systolic arterial blood pressure (Figure 2) and the cumulative dose of norepinephrine (89 (54-122) vs. 147 (116-242) µg, p < 0.001) during carotid cross-clamping were lower in the intervention group than in the control group. In all patients allocated to the intervention group, titration of norepinephrine was sufficient to restore regional brain tissue oxygen saturation.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The rate of carotid shunt placements was comparable between the intervention and control groups (7/30 (23.3%) vs. 4/30 (13.3%), respectively; p = 0.51). Although the duration of carotid cross-clamping did not differ between the intervention and control groups (37 (32-44) vs. 37 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) min, p = 0.98), systolic arterial blood pressure (Figure 2) and the cumulative dose of norepinephrine (89 (54-122) vs. 147 (116-242) µg, p < 0.001) during carotid cross-clamping were lower in the intervention group than in the control group. In all patients allocated to the intervention group, titration of norepinephrine was sufficient to restore regional brain tissue oxygen saturation.…”
Section: Resultsmentioning
confidence: 92%
“…Although the researchers conducting the neurocognitive tests were blinded to group allocation, we cannot exclude that a performance or investigator bias influenced the perioperative care of patients randomized to the intervention group. Fourth, the time point of eight weeks after surgery was chosen in line with other studies [38] assuming that patients had sufficient time to recover from the neurocognitive impact of surgery. However, we cannot exclude that testing neurocognitive function at a later time point following CEA [2] might have changed our results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported early changes in cognitive domains mainly at 1–6 months after CEA. Attention, memory, executive function, visuospatial orientation, psychomotor speed, and fluency have been reported to improve shortly after CEA 1,2,2427 , while language, working memory, and global cognition deteriorated 2,4,2830 . Only one study investigated the P300 evoked potential as a marker of cognitive function at 5 years after CEA in 25 patients, but detailed results for specific cognitive functions were not reported 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Available data clearly show that ACS patients should not be offered a "one-sizefits-all" approach (80). Moreover, it is often emphasized that a plaque considered as asymptomatic is not always so (symptoms may occur during sleep, cognitive decline) (80)(81)(82)(83). Taking into account the current state of knowledge and waiting for further development of pharmacological treatment, it should be stated that in selected asymptomatic patients (high risk of cerebral embolization; low risk of cardiac, pulmonary and other complications; acceptable life expectancy) carotid plaque should be removed as a potential source of emboli (5,80).…”
Section: Treatment Optionsmentioning
confidence: 99%